THE IMPACT OF LEADERSHIP STYLE, TRAINING AND ORGANIZATIONAL CULTURE RELATED TO THE EMPLOYEE PERFORMANCE AT BHAYANGKARA BRIMOB HOSPITAL, DEPOK - Trisna Nilasari, Fiky; Kasmir, Kasmir (Dinasti Publisher, 2021)
The intention of this research was to identify and reveal those impacts from leadership style, training, and organizational culture towards the employee performance of Bhayangkara Brimob Hospital at Depok. This research was included in quantitative research with causal method through cross-sectional methods to see the correlations between variables. The research population was all Medical Staff of Bhayangkara Brimob Hospital at Depok, with a total of 197 employees, while the sample in this research was 130 employees (through Slovin 5% error tolerance). The data collection method in this research used a review of damage and a field review, while the method of data analysis used multiple linear regression analysis to examine the hypothesis. The results showed that the leadership style, training, and organizational culture both partially and simultaneously affect the employee performance of the Bhayangkara Brimob Hospital at Depok.